Conocimiento de anticoncepción de emergencia en estudiantes del Colegio Ismael Pérez Pazmiño, cantón Machala. - Lima Morocho, Yesenia Beatriz (2017)
The emergency oral contraceptive emerges as an intervention initiative focused on health, taking into account that the beginning of a sexual relationship in the adolescent is increasingly young, where they are not yet ready and with the Sufficient information to cope with the repercussions of unprotected sexual intercourse, which involves unwanted and precocious pregnancy, as well as sexually transmitted diseases. The present investigation related to the knowledge about emergency contraception by the students of the third year of the high school of the Educational Unit Ismael Pérez Pazmiño was carried out in the city of Machala, period September 2016 - March 2017, whose objective Was to identify the level of knowledge about emergency contraception by adolescents. The design of the research is descriptive, the survey was applied as a survey to 150 students, the results determined that 95% of the population represent the female sex, of which 79% are single; Of the total number of men surveyed, half of them are single; 46% of the population are aware of the correct use of emergency oral contraceptives, indicating that they are used in cases of rape, unprotected sex, condom breakage, and forgetfulness of taking oral contraceptives; However, 47% of the population under study are unaware of the effect of these contraceptives and 51% know the side effects that causes such as: nausea, vomiting, dizziness, breast tenderness, headache, fatigue. In conclusion, the students of the Educational Unit mentioned above do not have adequate knowledge about emergency oral contraception. Key words: knowledge, use, emergency contraception.